2002
DOI: 10.1089/105072502760339307
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Transporter 1 Gene Expression is Related to Thyroid Neoplasms with an Unfavorable Prognosis: An Immunohistochemical Study

Abstract: These data indicate that overexpression of GLUT1 on the cell membrane of thyroid neoplasms is closely related to tumors demonstrating a more aggressive biological behavior. Therefore, determination of GLUT1 expression in thyroid cancer tissue may be a prognostic marker, and FDG-PET may be a helpful technique in identifying patients at a higher risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 22 publications
6
80
2
5
Order By: Relevance
“…As shown in finding is in keeping with the previously reported observation that GLUT1 overexpression correlates with more de-differentiated forms of thyroid tumor (Schonberger et al, 2002, Stokkel et al, 2006 that are, indeed, those with a higher ability to take-up 18 FDG (Conti et al, 1999, Khan et al, 2005.…”
Section: Analysis Of Glut1 and Glut3 Proteins On Cell Membrane And Cysupporting
confidence: 91%
See 2 more Smart Citations
“…As shown in finding is in keeping with the previously reported observation that GLUT1 overexpression correlates with more de-differentiated forms of thyroid tumor (Schonberger et al, 2002, Stokkel et al, 2006 that are, indeed, those with a higher ability to take-up 18 FDG (Conti et al, 1999, Khan et al, 2005.…”
Section: Analysis Of Glut1 and Glut3 Proteins On Cell Membrane And Cysupporting
confidence: 91%
“…As far as the GLUT1 and GLUT3 mRNA expression in thyroid tumor is concerned, our data support the results of the few reports that have been published up to date (Haber et al, 1997, Matsuzu et al, 2004, Schonberger et al, 2002 which showed a significant increase of GLUT1 and a slightly increase of GLUT3 mRNA levels in malignant thyroid tissues when compared to normals. The evidence of a decreasing pattern of mRNA expression levels of GLUT1 in cell lines accordingly to their pattern of dedifferentiation was confirmed in human thyroid tumors with ATC showing a higher expression than PTC and FTC.…”
Section: Analysis Of Glut1 and Glut3 Proteins On Cell Membrane And Cysupporting
confidence: 90%
See 1 more Smart Citation
“…As already shown in other tumor types, recent studies in thyroid cancer have demonstrated the prognostic significance of necrosis and proliferation, estimated by the number of mitoses (Akslen & LiVolsi 2000, Hiltzik et al 2006. Furthermore, immunohistochemistry may detect the expression of proteins involved in iodine metabolism (sodium iodine symporter (NIS), thyroglobulin (Tg), thyroid peroxidase (TPO), apical iodine transporter (AIT), and dual-oxidase (p138-DUOX)), FDG uptake (glucose transporter 1 (GLUT-1) and hexokinase; Dupuy et al 2000, De Deken et al 2002, Schönberger et al 2002, Lacroix et al 2004, and angiogenesis, such as vascular endothelial growth factor (VEGF) and VEGF receptor (VEGF-R) (Bunone et al 1999, Katoh et al 1999, Klein et al 2001, Lennard et al 2001). These three features were shown to be related to thyroid cancer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…В 2002 г. J. Schonberger и соавт. предположили, что ги-перэкспрессия Glut 1 на клеточной мембране связана с большей биологической агрессивностью РЩЖ [7]. Гиперэкспрессия Glut 1 была выявлена в 0-10 % слу-чаев фолликулярной аденомы, 52,9-100 % папилляр-ного РЩЖ, 33,3-58,8 % фолликулярного РЩЖ, 80 % плохо дифференцированного РЩЖ и практически во всех случаях анапластического РЩЖ [8].…”
unclassified